1993
DOI: 10.1007/bf00170000
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of the left ventricle is impaired in arrhythmogenic right ventricular disease

Abstract: Arrhythmogenic right ventricular disease (ARVD) is a disease of unknown origin that primarily affects the right ventricle and is characterized by ventricular tachyarrhythmias which may lead to syncope and even, though rarely, sudden cardiac death. In 25 patients with ARVD, sympathetic innervation of the left ventricle was assessed by iodine-123 metaiodobenzylguanidine single photon emission tomography (123I-MIBG SPET). In addition, thallium-201 SPET was performed. The diagnosis of ARVD was made by an electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The authors elaborated on 4 theories on the etiology of ARVD, potentially explaining the development and occurrence of the disease; the dysontogenic, degenerative, inflammatory, and apoptotic theory. Involvement of the left ventricle in ARVD had already been evidenced by Lerch et al [38] who showed impaired sympathetic innervation of the left ventricle in patients with ARVD. Accordingly, the disease should be regarded as a serious congenital heart disease.…”
Section: Pathogenesis/etiologymentioning
confidence: 65%
“…The authors elaborated on 4 theories on the etiology of ARVD, potentially explaining the development and occurrence of the disease; the dysontogenic, degenerative, inflammatory, and apoptotic theory. Involvement of the left ventricle in ARVD had already been evidenced by Lerch et al [38] who showed impaired sympathetic innervation of the left ventricle in patients with ARVD. Accordingly, the disease should be regarded as a serious congenital heart disease.…”
Section: Pathogenesis/etiologymentioning
confidence: 65%
“…) right ventricular dysplasia. 171 There is no established method for scoring SPECT 123 I-mIBG images, but analysis can be performed similar to the conventional 17-segment method used for MPI with generation of a summed score. 155 Nevertheless, an important consideration for 123 I-mIBG images is that when there is globally decreased uptake, that is, low HMR, homogeneous tracer uptake cannot be scored as normal as, unlike the custom for perfusion images, one cannot assume a "normal" region.…”
Section: Image Analysis and Interpretationmentioning
confidence: 99%
“…Myocardial ischemia and infarction produce regional efferent sympathetic denervation, which can be visualized by MIBG scintigraphy and may influence arrhythmias [134][135][136][137][138][139][140][141][142][143]. Abnormalities of sympathetic innervation, demonstrated by MIBG imaging, are frequent in patients with ventricular arrhythmias without apparent heart disease [144][145][146][147], in patients found with the congenital long-QT syndrome [148], and in those with arrhythmogenic right ventricular disease [149,150].…”
Section: Fig 3 Survival Curves With a Threshold Value Of 20% For Lementioning
confidence: 99%